Arterial hypertension: A neglected risk for bleeding. Issue 2 (August 2016) - Vogel, Birgit; Mehran, Roxana
Key points: The impact of arterial hypertension, one of the most common comorbidities in CAD patients, on bleeding risk after PCI must not be underestimated. More rigorous control of blood pressure during PCI procedure, radial artery access and alternative anticoagulant strategy may be considered in these patients. Further investigation in a more contemporary setting of PCI procedure is warranted.